2020
DOI: 10.3390/diagnostics10110869
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis of Pancreatic Cancer: The Key for Survival

Abstract: Pancreatic cancer (PC) is one of the most aggressive forms of cancer. Negative prognosis is mainly due to the late diagnosis in advanced stages, when the disease is already therapeutically overcome. Studies in recent years have focused on identifying biomarkers that could play a role in early diagnosis, leading to the improvement of morbidity and mortality. Currently, the only biomarker widely used in the diagnosis of PC is carbohydrate antigen 19-9 (CA19.9), which has, however, more of a prognostic role in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 105 publications
0
45
0
Order By: Relevance
“…At the moment there are two major types of blood data used in cancer diagnosis: genomic and proteomic. Genomic data can be epigenetic, circulating tumor DNA, MicroRNAs and stool-based tests [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the moment there are two major types of blood data used in cancer diagnosis: genomic and proteomic. Genomic data can be epigenetic, circulating tumor DNA, MicroRNAs and stool-based tests [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of their development in the same patient, should they be considered as two independent diseases, or one of them is a natural consequence of the other? Most studies of pancreatic exocrine function in diabetic patients have reported mild and moderate exocrine pancreatic insufficiency, which has been expressed in a relative decrease of bicarbonate and enzyme production, and severe pancreatic exocrine insufficiency with steatorrhea is relatively rare [35][36][37] . According to Sirchak et al, in patients with T2DM, CP is formed on the background of biliary pathology, while the functional capacity of the pancreas is greater than in T1DM 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances made in the last few decades in understanding PDAC biology and developing new targeted therapies [3][4][5][6], PDAC patients continue to have a dismal prognosis, with a 5-year survival rate of less than 20% [7,8]. Tumor stage is the main prognostic determinant, early-stage tumors being associated with a longer survival than that of locally advanced or metastatic tumors [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the PDAC setting, several studies in the literature have evaluated different miRNAs panels as diagnostic and/or prognostic tools by analyzing tissue expression [26,27], serum levels [24], blood levels [28] and ascitic fluid levels [25]. New biomarkers of PDAC should aid early diagnosis and, as prognostic indices in early-stage cases, should be helpful in distinguishing between patients with long or short life expectancies, thus allowing a more tailored therapeutic approach [7,29].…”
Section: Introductionmentioning
confidence: 99%